Proton exchange composite membranes comprising SiO2, sulfonated SiO2, and metal–organic frameworks loaded in SPEEK polymer for fuel cell applications. Issue 22 (2nd February 2021) - Bisht, Sanjay; Balaguru, Sasikumar; Ramachandran, Sathish Kumar; Gangasalam, Arthanareeswaran; Kweon, Jihyang
Abstract: Proton exchange membrane fuel cell (PEMFC) is a promising technology that offers a clean and efficient renewable energy source. The hybrid SiO2, sulfonated SiO2 (S SiO2 ), and metal–organic framework‐5 (MOF‐5) incorporated sulfonated poly (ether ether ketone) (SPEEK) ternary composite membranes are fabricated using dry phase inversion technique for PEMFC. The membrane performance is evaluated in terms of water uptake, ion exchange capacity, methanol permeability, and proton conductivity (PC) measurements. The morphological study of fabricated membranes was carried out using scanning electron microscopy and atomic force microscopy analysis. The mechanical stability is strengthened up to 30–40%, and the PC gets enhanced with the incorporation of MOF‐5, achieving simultaneous improvement in proton conduction and membrane stability. The PC of the ternary SPEEK/SSiO2 /MOF‐5 membrane is 3.69 × 10 −3 S cm −1, 32% more than the neat membrane. A significant increase in selectivity of 23% is observed by incorporating SSiO2 and MOF‐5 fillers when compared with the neat membrane. The synergistic effect of MOF‐5 and SSiO2 in the ternary membrane has significantly improved water retention and proton conductivity. The functional SO3 H groups of SiO2 and MOF‐5 bonded via acid–base electrostatic interactions with the SPEEK; enhances proton conduction accompanied by suppressing the methanol penetration through membranes. Abstract : Hybrid ternary composite membranes for proton conduction were reported using sulfonated SiO2 (S‐SiO2), and MOF‐5 incorporated SPEEK polymer. The combined effect of MOF‐5 with S‐SiO2 in the ternary membrane has enhanced water retention and proton conductivity. The fabricated membranes showed a significant improvement in the proton conduction due to the attachment of sulfonyl group and MOF‐5 bonded via acid‐base interaction with the SPEEK polymer matrix.